Pengaruh Manajemen Laba Dan Good Corporate Governane Terhadap Kinerja Keuangan Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Yang Terdafar Di Bursa Efek Indonesia Periode 2014-2016) - Suparman, Petrus; Ningtyas, Retno (GEMA EKONOMI, 2019)
The purpose of this study is to prove whether earnings management and Good Corporarate Governance affect the financial performance of the company. The research was conducted at manufacturing company of industrial sector of consumer goods listed in Indonesia Stock Exchange period 2014-2016. Analysis of data model used in this research is multiple linear regression model using SPSS 18. Data analysis using classical assumption test that is data normality test, multicolinierity test, autocorrelation test and hiteroskedatisitas test. And t test and f test. The results showed that there is no effect of earnings management on corporate financial performance. then the company's financial performance as measured by return on assets has increased with good corporate governance. The test results of both variable earnings management and good corporate governance have a positive and significant impact on the financial performance of the company.Keywords: earnings management, good corporate governance, financial performanceDOI :10.5281/zenodo.3474586